It’s Time to Beelieve the CD1a Hype! - Krovi, S. Harsha (Eur J Immunol, 2016)
Conventional T cells have historically been linked to exacerbating allergy. By efficiently generating primarily T(H)2 cells, allergens skew the immune response to produce IL-4, IL-13, and IgE. Previously, CD1a-responsive T cells were shown to functionally respond to bee and wasp venom allergens. In this issue of the European Journal of Immunology, Subramaniam and colleagues [Eur. J. Immunol. 2015. DOI: 10.1002/eji.201545869] show that more functionally active CD1a-restricted cells are present in bee venom allergic patients than in healthy patients. Additionally, the authors show that these cells are not as frequently found in individuals receiving venom immunotherapy. Consequently, this study implicates CD1a-reactive cells as the primary responders to venom allergy, which considerably regulate the downstream immune response.